Oportunidades de las minicadenas productivas del sector cacao de Santander frente al pos conflicto colombiano (2019)
The objective of this article was to analyze the op-portunities for mini-chains in the cocoa sector in the department of Santander in order to determine pos-sible options for insertion of cocoa products into global value chains in the post-conflict period. In order to fulfill this purpose, a descriptive methodology was implemented to determine the characteristics of the production chain of the cocoa sector in Santander through the application of the mini-productive chains model provided by the United Nations Industrial De-velopment Agency (UNIDO). By virtue of the analysis carried out, it could be determined that the cocoa sec-tor of the department of Santander has not been able to promote the generation of differential factors in the value chain due to the low technological development in the transformation operations, the lack of knowl-edge of the quality parameters on the part of the links of producers and marketers, the lack of knowledge of the requirements of the international markets and the problems of associativity, trust and integration of the links of the chain. In response to the aforementioned weaknesses, Colombia's public policies have prioritized cocoa as a raw material of interest for rural development, deploying governmental and international cooperation actions aimed at consolidating an adequate value chain and thus solving the technological and organizational needs of a key agricultural sector in the process of substitution of illicit crops in the post-conflict period.